ʺMechanisms for Implementing Compliance Management Approaches in the Higher Education Systemʺ - Hrinchenko, H.; Nesterenko, R.; Fomenko, A. (Problems of Engineer-Pedagogical Education, 2024)
The article proposes mechanisms for implementing compliance management approaches in the system of higher education, namely in higher education institutions. The structure of the compliance management system is proposed, which includes several key elements, such as: creation of compliance policies and procedures, organisation of the control and audit system, creation of internal control bodies, education and training of personnel, information support, stimulation of responsible behaviour, cooperation with external organisations and establishment of partnerships with state control bodies, professional associations and other stakeholders to share experience and use best practices. The integration of the proposed elements of the compliance management system is proposed taking into account the existing regulatory documents, both external and internal. The article considers the mechanisms for implementing the components of the compliance management system for the Ukrainian Engineering and Pedagogical Academy on the example of the existing regulatory support within the HEI. Positive aspects of the implementation of mechanisms and further development of the compliance management system in the direction of training and education of staff in the principles and approaches based on the development of a special microcredit course are identified. As recommendations for improving the existing quality management system, it is proposed to increase information support for the implementation of the proposed measures, which will contribute to the formation of responsibility. It is noted that the introduction of compliance management principles in the higher education system is a promising area of research, since this approach contributes to the effective implementation of the requirements of legislation, standards and policies in the field of education. Compliance management contributes to the creation of a system of control, audit and internal supervision that ensures compliance with regulatory requirements and reduces the risk of violations. In addition, this approach promotes the formation of an ethical culture and responsibility among participants in the educational process. Implementation of compliance management can improve the quality of education, increase public trust, enhance the competitiveness of the institution and ensure the stability of the management of the higher education institution.